Impact of Moderate-To-Vigorous Sports Participation Combined with Resistance Training on Metabolic and Cardiovascular Outcomes among Lean Adolescents: ABCD Growth Study - von Ah Morano, Ana Elisa [UNESP]; Torres, Wésley [UNESP]; Zancheti, Eduardo [UNESP]; Wigna Pereira de Jesus, Andrea [UNESP]; Bexiga Urban, Jacqueline [UNESP]; Fernandes, Romulo Araújo [UNESP] (MDPI, 2023)
Background: To investigate the combined impact of being engaged in resistance training (RT) and meeting the physical activity guidelines through sports participation (SP) on cardiovascular and metabolic parameters in lean adolescents. Methods: A longitudinal study, part of the ongoing study entitled “ABCD Growth Study” (Analysis of Behaviors of Children During Growth), assessed data from 64 adolescents (23 from the sport group, 11 from the sport + RT group, and 30 from the control group). Metabolic and cardiovascular outcomes were analyzed as dependent variables. For the independent variables, sports participation and resistance training were considered, and for the covariates, sex, chronological age, body weight, height, and somatic maturation. Results: After 12 months of follow-up, the RT + SP presented improvements in triglycerides (TG) and the SP presented a reduction in LDL-c, TG, and glucose when compared to the control group. Conclusions: Being engaged in RT and SP is a good strategy to improve health in eutrophic adolescents, with a great impact on TG from the lipid profile.
Keywords: exercise; pediatrics; risk factors